AN ERROR ANALYSIS OF SIMPLE PAST TENSE IN WRITING NARRATIVE TEXT AT SECOND GRADE SMAN 1 CIOMAS - Chotibul Umam (FKIP, Universitas Banten Jaya, 2018)
The objectives of this study were to identify whether the students make errors and to find the types of errors made by the second grade of SMAN 1 Ciomas in Simple Past Tense in their Narrative Text. The classification of the types of the error of the study was based on Dulay, and the procedure of error analysis used Ellis’ procedure. In this study, the writer used content analysis method to describe students’ error and analyze the data. The data which were taken from the test focus on Simple Past Tense. The sample of this study was the students of second grade of SMAN 1 Ciomas, in academic year 2015/2016, the class XI IPA consisting of 33 students. Procedure of this study was 68 errors and identifying, describing, recapitulating. The result of this study made errors in misformation (30 or 44.11%), addition (14 or 20.58%), misordering (13 or 19.11%), and omission(11 or 16.17%). Based on the study, the writer concludes that the second grade students of SMAN 1 Ciomas, most of students made errors in using Simple Past Tense, and the classification type of error was in misformation.